2011
DOI: 10.1002/humu.21408
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of colorectal cancer risk on the parent-of-origin of mutations in DNA mismatch repair genes

Abstract: Genetic diseases associated with dynamic mutations in microsatellite DNA often display parent-of-origin effects (POEs) in which the risk of disease depends on the sex of the parent from whom the disease allele was inherited. Carriers of germline mutations in mismatch repair (MMR) genes have high risks of colorectal carcinoma (CRC). We investigated whether these risks depend on the parent-of-origin of the mutation. We studied 422 subjects, including 89 MMR gene mutation carriers, from 17 population-based famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
1
11
1
Order By: Relevance
“…8,9 However, a trend was observed toward a lower HR for CRC in females with a paternally inherited mutation. This is broadly in line with the results of van Vliet et al 8 for the males in their research population, although their results showed a much higher, and significant, HR of 3.2 (P = 0.03) for males when comparing maternally inherited mutations with paternally inherited mutations.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…8,9 However, a trend was observed toward a lower HR for CRC in females with a paternally inherited mutation. This is broadly in line with the results of van Vliet et al 8 for the males in their research population, although their results showed a much higher, and significant, HR of 3.2 (P = 0.03) for males when comparing maternally inherited mutations with paternally inherited mutations.…”
Section: Discussionmentioning
confidence: 91%
“…A possible explanation for the differences in POE findings could be the fact that van Vliet et al 8 used another statistical approach-a modified segregation analyses. We did not use this broad approach because, to the best of our knowledge, no bias or confounders were present in our cohort that would make a modified segregation analysis necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it was shown that the paternal germline is more mutagenic than the maternal one with respect to base substitutions and replication slippage errors at microsatellites (Sun et al, 2012). It is also known that carriers of germline mutations in mismatch repair (MMR) genes in humans are prone to get colorectal cancer and that the risk depends on the parent-of-origin of the mutation (van Vliet et al, 2011). The molecular basis of these parental effects is not entirely clear but is likely to involve higher rates of nondisjunction during female meiosis, higher mutation rates during spermatogenesis, and probably additional effects of aging.…”
mentioning
confidence: 99%